Influenza vaccination reduces hemorrhagic stroke risk in patients with atrial fibrillation: A population-based cohort study. (1st April 2017) - Liu, Ju-Chi; Wang, Ta-Jung; Sung, Li-Chin; Kao, Pai-Feng; Yang, Tsung-Yeh; Hao, Wen-Rui; Chen, Chun-Chao; Hsu, Yi-Ping; Wu, Szu-Yuan
Abstract: Purpose: The risk of hemorrhagic stroke in patients with atrial fibrillation (AF) is low but the consequences of its occurrence are extremely severe. In this study, we investigated the association of influenza vaccination with the risk of hemorrhagic stroke to develop an efficient strategy for reducing this risk in patients with AF. Methods: In this study, data were retrieved from the Taiwan National Health Insurance Research Database. The study cohort comprised all patients who received a diagnosis of AF ( n  = 14, 454) before January 1, 2005 (index date) and were followed until December 31, 2012. Propensity scores were calculated using a logistic regression model to determine the effects of vaccination by accounting for covariates that predict receiving the intervention (vaccine). A time-dependent Cox proportional hazard model was used to calculate the hazard ratios (HRs) for hemorrhagic stroke in vaccinated and unvaccinated patients with AF. Results: The study population comprised 6570 patients who did (2547 [38.77%]) and did not receive (4023 [61.23%]) influenza vaccination. The adjusted HRs (aHRs) for hemorrhagic stroke were lower in the vaccinated patients than in the unvaccinated patients (influenza season, noninfluenza season, and all seasons: aHRs = 0.97 [0.59–1.60], 0.51 [0.30–0.87], and 0.72 [0.50–1.03], respectively). Conclusions: Influenza vaccination exerts dose–response and synergistic protective effects against hemorrhagic stroke in patients with AF who have a high risk of hemorrhagic stroke (i.e., male sex, age ≥ 75 years, Charlson comorbidity index ≥ 3, and hypertension) and reduces the incidence of hemorrhagic stroke.